Problems and Prospects of Sugar Industry in India: Case Study of Bijnor District; Uttar Pradesh - Gangwar, Deepa; Misra, Roli (International Journal of Social Sciences and Management, 2023)
The sugar industry is the most vital industry in India as well as in Uttar Pradesh. Its importance in the state can also be known from the fact that Uttar Pradesh is called the sugar bowl of India. The processing of sugar production is done by co-operative sugar mills and private sugar mills and both the mills are equally important for the bright future of the sugar industry in Uttar Pradesh. In this study, we have attempted to compare and contrast private and cooperative sugar mills. For this, we selected the largest sugarcane-producing area in western Uttar Pradesh, the Bijnor district. This paper is based on both primary data collection and secondary data collection. Primary data was collected through field survey which was undertaken to Dhampur Chini Mill, a privately owned mill with the maximum capacity for crushing sugarcane, and Snehroad Najibabad Mill, a cooperative sugar mill with the lowest capacity. Comparing both the mills it was found that private mill Dhampur is superior in terms of infrastructure, cane crushing capacity, sugar output, and ethanol production. It is more conscious of its corporate social and environmental responsibilities. The cooperative sugar mill doesn't have power cogeneration unit, which should be established, and it makes less revenue than the Dhampur sugar mill generates. The paper concludes with specific policy suggestions to improve condition of cooperative mills. Int. J. Soc. Sc. Manage. Vol. 10, Issue-1: 16-24.